Pengaruh Aktivitas Fisik Sedang Terhadap Nilai Mean Arterial Pressure (Map) Pada Mahasiswa Obesitas Grade II - Ahmad Haydar Rusdiansyah (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2019)
Obesity is a health problem that continues to increase every year and triggers double burden nutrition problems. The prevalence of obesity in Indonesia in 2013 reached 32.9% and 19.7% for women and men. Subjects with hypertension who have moderate-intensity physical activity show a significant decrease in blood pressure and Mean Arterial Pressure (MAP). This study aims to determine the effect of moderate-intensity physical activity on MAP in grade II obese college students. This research is a paired comparative analytic study with a quasi-experimental design. The method used was pretest-posttest design without a control group. The statistical analysis used was paired t-test and independent t-test. This research was conducted in November 2019 by giving a 30 minutes brisk walking to the respondent's Respondents were grouped into a group of grade II obesity and normal BMI. The results showed the mean pre-test and post-test MAP in the obesity group were 101.3 and 102.3 mmHg and the mean pre-test and post-test MAP in the normal IMT group were 91.3 and 89.1 mmHg. Based on the results of statistical tests, doing once the moderate-intensity physical activity has no significant effect on changes of MAP in obese college students with a p-value of 0.557. cell damage and increasing insulin sensitivity and helping the action of liver regulating enzymes.